Bizarre cell dysplasia of the cervix. Issue 2 (February 2017) - Ondič, Ondrej; Ferko, Radoslav; Kašpírková, Jana; Švajdler, Marián; Rýchly, Boris; Talarčík, Peter; Bouda, Jiří; Michal, Michal
Abstract: Aim: The aim of this study was the characterization of a new subtype of high‐grade cervical squamous intraepithelial lesion (HSIL) with enlarged cells containing bizarre nuclei: so‐called bizarre cell dysplasia (BCD). Methods: A total of 29 cervical cone biopsy samples of this type of dysplasia were studied. Multi‐target polymerase chain reaction and in situ hybridization human papillomavirus (HPV) detection was performed in all cases. BCD was defined as a subtype of HSIL characterized by the presence of large dysplastic cells with abnormal, large pleomorphic nuclei or multinucleation causing nucleomegaly. This results in bizarre nuclear shapes. Bizarre cells are scattered throughout the whole thickness of the dysplastic squamous epithelium. Results: The BCD lesions arise within the conventional/classic high grade or "bland" type squamous dysplasia HSIL. Statistically they were significantly associated with HVP type 16. A significant association with other studied viruses (Herpes simplex virus [HSV]1, HSV2, Varicella zoster virus, Epstein–Barr virus, cytomegalovirus, human herpesvirus 6, and human polyomaviruses BK and JC) was not confirmed. Conclusions: BCD involves cytologically characteristic morphologic changes that are recognizable, but which may pose some risk of misdiagnosis as low‐grade squamous intraepithelial lesion due to the enlargement of dysplastic cells and multinucleation. Based on the unique histological, cytological and biological features of BCD including strong association with HPV 16 infection, we believe that this is a specific, and so far unrecognized variant of HSIL.